Kepemimpinan Pembelajaran Matematika SMK - Anam Sutopo; Eko Rubiyanto (Manajemen Pendidikan, 2019)
This study aimed to describe the effectiveness leadership of teachers in mathematicslearning in class XI SMK Country 2 Surakarta School Year 2017/2018. This typeof research is qualitative research . The subjects of the recipient of the action werestudents of class XI SMK Country 2 Surakarta 3 classes, namely XI TPM D, XITKBB, XI TKR A which amounted to 90 students and the subject of the action wasthe researcher assisted by a mathematics teacher. Method of collecting data throughobservation, interviews, field notes and documentation. Data analysis techniques werecarried out descriptively qualitative with a flow model consisting of date collection,data reduction, data presentation, verification and conclusion drawing. The resultsof this study indicate that by approaching students, understand the character ofstudents so that they feel close, not acute with the teacher , dare to ask questionsabout mathematical competencies that have not been understood, and feel cared foracknowledged by students who have the ability and skills.